The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.2489/jswc.65.4.252
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic modeling of runoff from a livestock manure windrow composting site with a fly ash pad surface and vegetative filter strip buffers

Abstract: Windrow composting of livestock manure materials provides a strategy for converting organic wastes into a recyclable soil fertility product that is less hazardous to the environment. Although outdoor windrow composting can produce runoff that is detrimental to surface water quality, vegetative filter strip (VFS) buffers were reported to significantly reduce runoff and contaminants from a windrow composting research site. To estimate the efficacy of VFS buffers and other best management practices on runoff from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Although extensive research has been conducted on BS in recent years (Webber et al 2010;Dunn et al 2011;Larson and Safferman 2012;Wang et al 2012), there is still a need to clarify some controversial points. First, it is well known that BS width may be positively correlated to N removal effectiveness.…”
Section: Introductionmentioning
confidence: 98%
“…Although extensive research has been conducted on BS in recent years (Webber et al 2010;Dunn et al 2011;Larson and Safferman 2012;Wang et al 2012), there is still a need to clarify some controversial points. First, it is well known that BS width may be positively correlated to N removal effectiveness.…”
Section: Introductionmentioning
confidence: 98%
“…Several studies assessing the effectiveness of VFS in intercepting and treating surface runoff have shown that the efficacy of this BMP is influenced by several factors, including the VFS length and width (Wenger, 1999;Zreig et al, 2004), the ratio of runoff source area to VFS area (Dosskey et al, 2011), the VFS buffer species (Ree, 1949;Broadmeadow and Nisbet, 2004), VFS nutrient and sediment trapping (Meyer et al, 1995;Van Dijk et al, 1996;Gharabhaghi et al, 2001;Zreig, 2001;Lee et al, 2003;Webber et al, 2010aWebber et al, , 2010b, VFS performance (Dosskey et al, 2007), concentrated surface flow (Dosskey et al, 2002), and chemical and nutrient concentrations in runoff (Arora et al, 1996(Arora et al, , 2003Boyd et al, 2003;Webber et al, 2009).…”
mentioning
confidence: 99%